1997
DOI: 10.1088/0953-8984/9/19/014
|View full text |Cite
|
Sign up to set email alerts
|

A Mössbauer study of , having the olivine structure: comparison with fayalite and related minerals

Abstract: has the olivine structure Pnma with , and at room temperature. The Mössbauer spectrum at 295 K consists of two doublets having centroid shifts (relative to ) and quadrupole splittings for the two metal positions Fe1 (point symmetry ) and Fe2 (point symmetry m) of , and . A point charge calculation for the nearest S octahedra gives the Mössbauer asymmetry parameters and for Fe1 and Fe2 respectively, and for both positions. At approximately 130 K there is an antiferromagnetic transition, and a second transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Furthermore, it was shown that the difference in centroid shift value for the two sites was CS(M2) ^CS(M1) % 0.04 mm/s for all samples at room temperature. The same result can be derived from earlier studies of Fe 2 SiS 4 in the AFM region [7]. The same difference in CS-values is also found in the AFM region for the 5% Co and 5% Ni samples.…”
Section: 22supporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, it was shown that the difference in centroid shift value for the two sites was CS(M2) ^CS(M1) % 0.04 mm/s for all samples at room temperature. The same result can be derived from earlier studies of Fe 2 SiS 4 in the AFM region [7]. The same difference in CS-values is also found in the AFM region for the 5% Co and 5% Ni samples.…”
Section: 22supporting
confidence: 89%
“…Substitution with Co and Ni increases T N : A detailed study of the Mossbauer absorption pro¢les gave T N 126 K for Fe 2 SiS 4 , 132 K for (Fe 0.75 Co 0.25 ) 2 SiS 4 and 155 K for (Fe 0.75 Ni 0.25 ) 2 SiS 4 . Avery big difference in hyper¢ne ¢elds for iron at M1 and M2 in the AFM phase, as already found for Fe 2 SiS 4 [7] is also seen here for all samples, e.g. at T % 10 K, (Fe 0.75 Ni 0.25 ) 2 SiS 4 has B(Ml) % 30 tesla and B(M2) % 6 tesla.…”
Section: 22supporting
confidence: 87%
See 2 more Smart Citations
“…The arrangement of the atoms in the crystal is very closely packed and resembles hexagonal close packed arrangement. Among the olivine structures, F e based olivines are well known because of their diverse magnetic nature at low and high temperatures [2,3,4]. In the case of Fe 2 GeS 4 , it was found to possess weak ferromagnetic nature upto 69 K, anti-ferromagnetic nature between 69-143 K and above this temperature it is reported to be in paramagnetic nature [5].…”
Section: Introductionmentioning
confidence: 99%